REVIEW OF TYPES OF FINANCIAL TECHNOLOGY (FINTECH) IN INDONESIA: UNDERSTANDING SERVICES AND THEIR IMPACT - Mardiana; Muhammad Fauzan (Indragiri Research Center (ingreat), 2024)
This study aims to identify the various types of financial technology (fintech) operating in Indonesia and analyze their impact on financial inclusion. Utilizing literature review and secondary data analysis from reputable sources, the research reveals that a diverse range of fintech, including digital wallets, peer-to-peer lending, crowdfunding, digital banks, and market aggregators, has seen significant growth in Indonesia. Each fintech type offers unique services that enhance the accessibility of financial services for the public, particularly for underserved segments of the population. The findings indicate that digital wallets have become a popular choice for daily transactions, facilitating payments and enhancing user convenience. Peer-to-peer lending platforms provide crucial financing options for individuals and small businesses who may struggle to access traditional bank loans. Crowdfunding enables entrepreneurs to raise capital from a wide audience, fostering innovation and community support. Moreover, the study highlights the varying business models within the fintech landscape, which include transaction fees, interest income from loans, and partnerships with merchants. These models illustrate the adaptability of fintech solutions in responding to the evolving needs of consumers. By shedding light on the dynamics of the fintech industry and its role in promoting financial inclusion, this research contributes valuable insights for stakeholders, including policymakers, industry players, and consumers. The study underscores the importance of fostering a supportive regulatory framework to ensure sustainable growth and responsible innovation in the fintech sector in Indonesia.